2001
DOI: 10.1053/jhep.2001.24373
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Cholesterol Hypersecretion in Gallstone–Susceptible Mice Is Associated With Hepatic Up–Regulation of the High–Density Lipoprotein Receptor Srbi

Abstract: Enhanced hepatocellular trafficking of cholesterol to the bile canaliculus and cholesterol hypersecretion appears critical for gallstone formation. Therefore, we studied in more detail the hepatic cholesterol transport pathways in a mouse model of cholesterol gallstone disease. Biliary lipid secretion rates, plasma lipoprotein levels, hepatic expression of lipoprotein receptors, lipid regulatory enzymes, and putative cholesterol transporting proteins were analyzed in gallstone-susceptible C57L/J and gallstone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 66 publications
6
42
0
1
Order By: Relevance
“…A similar increase in the proportion of large HDL 1 particles is also observed with partial (40) or total (41) SRBI deficiency. Consistent with our finding, SRBI expression is induced in the liver of C57L/J mice upon cholic acid feeding (38). In the present report, we also showed that cholic acid positively regulates SRBI mRNA and protein expression in the liver of wild-type but not in that of FXR(Ϫ/Ϫ) mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar increase in the proportion of large HDL 1 particles is also observed with partial (40) or total (41) SRBI deficiency. Consistent with our finding, SRBI expression is induced in the liver of C57L/J mice upon cholic acid feeding (38). In the present report, we also showed that cholic acid positively regulates SRBI mRNA and protein expression in the liver of wild-type but not in that of FXR(Ϫ/Ϫ) mice.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our data, Fuchs et al (38) demonstrated that gallstonesusceptible C57L/J or gallstone-resistant AKR mice had similar apoA-I mRNA and protein levels when placed either on chow or on 0.5% cholic acid diet. In contrast, Claudel et al (14) reported that administration of the FXR agonist taurocholate repressed apoA-I expression in human hepatoma HepG2 cells as well as in human apoA-I transgenic mice.…”
Section: Discussionsupporting
confidence: 92%
“…3D illustrates that the increase (2.4-fold) of SR-BI expression in Abcb11 transgenic mice is 60% greater than the increase of SR-BI expression in wild-type mice (p Ͻ 0.01). These data are also consistent with previous data reporting a significant hepatic induction of the SR-BI receptor in response to the lithogenic diet (22). In contrast, the expression levels of Abcb11 (Fig.…”
Section: Expression Of Bile Salt and Cholesterol Metabolic Andsupporting
confidence: 93%
“…ApoB-containing lipoproteins (LDL and very-low-density lipoprotein) from the circulation, while SRB1 promotes selective uptake of HDL-cholesterol into the liver (9). Although increases in the expression of these genes may be expected to increase cholesterol secretion into the bile, the expression of Cyp27 was also elevated in the EX mice.…”
Section: Exercise and Gallstonesmentioning
confidence: 99%